Expanding the Forensic Use of the Acid Phosphatase Test: Rapid Detection of Saliva, Earwax, and Sweat under varied Environmental Conditions - Gupta, Geeta; Saini, Sanskriti (Journal of Neonatal Surgery, 2025)
The Acid Phosphatase (AP) test has long been used in forensic investigations to detect semen, but this study shows that it can also identify saliva, earwax, and sweat, making it a potentially more versatile tool. We analysed how AP activity responds in different body fluids under various conditions, including temperature changes (-20ºC, 4ºC, room temperature(+25ºC)) and exposure to humidity, dryness, and UV light, effect of surfaces absorbent Vs. non-absorbent for over 30 days. The results revealed that saliva and earwax produce an immediate reaction, making them easy to detect. Sweat also shows a positive result, but it takes more than a minute to appear. Even after long-term exposure to different environmental conditions, saliva and earwax samples continued to react instantly, demonstrating the durability of AP activity. We also found that cold temperatures help to preserve AP activity, while hot, dry conditions cause it to fade faster. The type of surface also matters—absorbent surface holds onto AP activity better than non-absorbent surfaces like glass, making it more useful in forensic evidence collection. These findings suggest that the AP test could be used for more than just semen detection, as it provides a rapid, reliable, and widely applicable forensic tool for detecting multiple biological fluids, thereby improving crime scene investigations and evidence analysis. However, since several fluids can test positive, forensic investigators should further confirm the results using more specific tests such as immunochromatography based approach or mRNA analysis, especially in sensitive cases like sexual assault investigations. This study highlights the need to further explore the forensic potential of the Acid Phosphatase (AP) test beyond semen detection, particularly in identifying and preserving other biological fluids like saliva, earwax, and sweat. Additionally, developing standardized protocols for field applications can improve its effectiveness in crime scene investigations and forensic evidence collection.